Allelopathic Mechanisms in Fire-Prone Ecosystems - Aktepe, Nursema; Küçük, Ömer (Turkish Science and Technology Publishing (TURSTEP), 2021)
Understanding the fire-prone arid-zone pine species and maquis vegetation's response to fire is very important to reveal the ecology and evolution of these species. During the succession of vegetation, there are complex relationships between allelopathic metabolites and fires. Many plant communities such as pines, maquis, savannas and woodlands are known to play a critical role in the development of succession. However, studies revealing the relationship between succession processes and allelopathic mechanisms in fire-prone ecosystems are quite limited. Most evergreen maquis vegetations are one of the most studied fire ecosystems. In maquis vegetation, fire causes the formation of plant communities that continue with allelochemicals produced by plants, as well as shaping the climate of the region. The event of a living species inhibiting another species by secreting toxic compounds is expressed as allelopathy. These toxic compounds are generally referred to as allelochemicals. Many maquis species that grow in fire-prone ecosystems excrete their allelochemicals, preventing the development of herbaceous species around them and invade their habitats. These chemicals, which accumulate in the soil during the dry season, affect the succession processes in vegetation in the event of a fire and determine which species will follow each other. Considering these relationships, it can be said that allelopathic plants have the potential to change plant diversity in vegetation by changing their functional plant characteristics. The purpose of this review is to determine the relationship between allelochemicals and fire of plant species in fire-prone ecosystems, and to reveal how this affects the succession processes.
Keywords: fire ecology; fire prone ecosystems; S; Agriculture (General); allelopathy; Agriculture; succession; S1-972; 15. Life on land